Facile and efficient synthesis of chiral sulfoxide esters: Versatile tool in asymmetric synthesis. Issue 2 (17th January 2019) - Nagpal, Reshma; Bhalla, Aman; Bhalla, Jitender; Bari, Shamsher S.; Thapar, Renu
Abstract: Facile and efficient synthesis of sulfoxide esters using menthols as chiral auxiliary is described. Phenylthio/benzylthio/naphthylthioacetic esters act as an efficient substrate for chiral sulfoxides via oxidation in one step. The structural and stereochemical aspects of target product were established on the basis of various spectroscopic studies, namely FT-IR, NMR ( 1 H NMR and 13 C NMR) and elemental analysis. This method is simple, fast, convenient and very efficient. Graphical Abstract: